Russian Institute for Advanced Study as a New Form of Training of Highly Trained Teaching Staff - Vsevolod V. Andreev (National Research Mordova State University, 2017)
Introduction: the aim of the paper is the analysis of role and capabilities of the Russian Institute for Advanced Study under Moscow State Pedagogical University in preparation of the top qualification scientific and teaching staff, possessing not only high potential in the narrow specialisation, but also inter- and transdisciplinary knowledge. The necessity for such staff is caused by rapid growth of scope and rates of new scientific knowledge accumulation, and, as a result, by development on their basis of new technologies in all sectors and by intensive introduction of such developments into all spheres of human activities. Materials and Methods: the processing of results of survey by the questionnaire method, as well as the synergistic and systemic approaches in their analysis and generalization, constituted the methodological basis for this study. Results: by analysis and generalisation of survey results it was shown that the Russian Institute for Advanced Study is unique form of training of top qualification scientific and teaching staff. The most important role of the Russian Institute for Advanced Study functioning format in implementation for Institute’s tasks is shown. During the work period at the Russian Institute for Advanced Study scientific and pedagogical employees are having unique possibility for finding non-standard approaches and methods for solving various problems, arising during projects implementation and which can’t be solved due to formal limitations of the traditional education system. Discussion and Conclusions: it is shown that the structure and principles of the Russian Institutes for Advanced Study functioning provide preparation of scientific and pedagogical staff of the highest qualification. The requirement for expanding Institutes for Advanced Study network in Russia is discussed. The results obtained represent practical importance for researchers engaged in the analysis of inter- and transdisciplinary knowledge role in the training of scientific and pedagogical staff. Further studies in this area can be devoted to analysis and generalization of inter- and transdisciplinary approach in the training of highly qualified scientific and pedagogical staff.